Empowering Schools in The Use of Interactive Multimedia as a Learning Media - Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2025)
Learning media is an important part of the classroom learning process. The appropriate use of interactive media can increase interaction in learning. This study aims to empower vocational schools in the use of interactive multimedia as an innovative learning medium. Through a training and mentoring program at SMK Negeri 1 Tondano, this activity focuses on improving teachers' digital literacy and students' learning motivation in Informatics subjects. The research method uses quantitative and qualitative approaches through surveys, observations, and knowledge tests. The results show a significant increase in teacher competence in developing Android-based media using Smart Apps Creator 3, as well as an increase in student learning motivation of more than 70%. This study contributes to the digital transformation strategy of vocational schools towards adaptive and participatory 21st-century learning. The impact of using interactive media can improve learning outcomes, make it easier for teachers to teach material in class more interactively, and make school more enjoyable for students.